Quantitative microbial risk analysis to evaluate health effects of interventions in the urban water system of Accra, Ghana - Labite, H.; Lunani, I.; Steen, P. van der; Vairavamoorthy, Kalanithy; Drechsel, Pay; Lens, P. (IWA Publishing, 2010)
A quantitative microbial risk assessment was applied to evaluate the microbial risks of the Accra Urban Water System (AUWS). The exposure assessment was based on the count of indicator organisms in waste water from open roadside drains and in water and sand samples from the beach. The predicted total disease burden generated in a representative catchment of the AUWS (Odaw Catchment) was 36,329 Disability Adjusted Life Years (DALYs) per year, of which 12% and 88% are caused by, respectively, shortcomings in the water supply system and inappropriate sanitation. The DALYs per person per year were above the WHO reference value. The open roadside drain had the highest contribution to the disease burden. Of four possible interventions evaluated for health risk reduction, the highest efficiency in terms of DALYs averted per euro invested are achieved by providing covers for the open roadside drains.